KOСOВEЛ И НИГИЛИЗМ: ПОПЫТКА КОНСТРУКТИВНОЙ ДЕСТРУКЦИИ (Filološke studije, 2019)
The paper proceeds with the question of Kosovel’s attitude towards nihilism. More precisely: what Kosovel understood under this term, which he was acquainted with and himself used, and in what sense did he try to transcend the subject of nihilism. In this context, the discussion primarily turns on Kosovel’s attitude towards Nietzsche, as far as it can be reconstructed with the help of Kosovel’s own formulations in his letters and dairy entries. On the bases of these, it is possible to advance the thesis that the alternative to nihilism for Kosovel was not «will to power» as the active life principle in Nietzsche’s sense. Kosovel’s aspirations followed a different path. Namely, the poet spoke of the ethical revolution, which was simultaneously a spiritual revolution, but not in the name of superman as an exposed, isolated figure of will to power, but in the name of new man, new humanity and its moral attributes. If Nietzsche abolishes the moral differentiation between good and bad and morality as such (morality is immoral), Kosovel’s endeavours go in the opposite direction: he aspires for a pronounced ethical and moral stance, since man – man as an ethical subject – needs to decide between good and bad, justice and injustice every time anew. It is in this light Kosovel’s formulation of man as «ethos incarnate» should be understood. Nietzsche is not the key figure to open the doors into Kosovel’s poetic world. And yet in Kosovel’s perception of Nietzsche there is some kind of a significant ambivalence. This ambivalence was in a way bolstered by what could be referred to as an unintentional misreading of Nietzsche.